Special Delivery to Wah-sut: An Eighteenth Dynasty Ostracon’s Inventory of Precious Materials - Justl, Shelby.
The following publication analyzes Ostracon SA. 2708 discovered during 2001 University of Pennsylvania Museum excavations in the ancient South Abydos town, Wah-sut. The ostracon enumerates a local delivery of unworked precious and semiprecious materials including gold, lapis lazuli, and jasper during the Eighteenth Dynasty. The ostracon provides a glimpse into the development and continued occupation of Wah-sut from the late Middle Kingdom into the New Kingdom and reveals evidence of deliveries of semiprecious stones in South Abydos not otherwise represented in the archaeological record. doi: http://dx.doi.org/10.5913/jarce.52.2016.a015